Electronic Nicotine Delivery Systems (ENDS): Implications for the Clinician - Jean-Guillaume Starnini; Giulio Natalello; Federico Nigroli; Chiara Diana; Elena Bargagli; Andrea Sisto Melani (Pulmonary Therapy)
Abstract The evidence that tobacco cigarettes are harmful to the health of smokers led to the introduction of electronic nicotine delivery systems (ENDS) as a safer alternative. ENDS, which include electronic cigarettes (e-cigs) and heated tobacco products (battery-operated devices that heat a liquid and produce an aerosol), are portable, cheap, easy-to-use, self-powered devices, and resemble tobacco cigarettes. After an overview of the toxicological, clinical, and epidemiological implications associated with the increasingly widespread use of ENDS, this narrative paper evaluates their role as a smoking cessation aid. Randomized controlled trials show that e-cigs can help in achieving cigarette smoking cessation, but their role in real life is still debated. There is no clear association in current smokers between the prevalence of e-cig use and overall quit rates. Although ENDS are not Food and Drug Administration (FDA)- and European Medicines Agency (EMA)-approved for quitting, they are one of the most widely utilized pharmacological support devices for smoking cessation. Physicians should ask for ENDS use and amount at each visit, be able to advise on how to manage ENDS as an aid for quitting, encourage vapers not to continue their use indefinitely, and explain how to stop ENDS.